2022
DOI: 10.1002/smtd.202200325
|View full text |Cite
|
Sign up to set email alerts
|

Impedance‐Enabled Camera‐Free Intrinsic Mechanical Cytometry

Abstract: and isotopes), requiring tedious sample preparation, invasive operation, and prior knowledge of cell specificity. [3] In contrast, biophysical methods measure the mechanical, electrical, and optical properties to perform quick, label-free, and non-invasive single-cell characterization, [4] so as to facilitate subsequent operations on cells such as sorting, [5] culturing, [6] and omics analysis. [7] Cellular biophysical properties have been proven as effective biomarkers for diagnosing diseases and widely used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 40 publications
2
25
0
Order By: Relevance
“…177 After calibration with agarose gel particles, a power-law rheology (PLR) model was used to represent cell creeping in the constriction channel to extract quantitative information on cell elasticity and fluidity of leukaemia cells (HL-60). To avoid the use of expensive high-speed cameras, researchers have developed impedance-based detection methods to profile cell biophysical properties by quantifying the cell geometrical change, 178 or cell creeping process 179 in an optics-free and label-free manner. A recent study was reported by Petchakup et al who defined a novel "electrical deformability index" for single cell electro-mechano-phenotyping (Fig.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…177 After calibration with agarose gel particles, a power-law rheology (PLR) model was used to represent cell creeping in the constriction channel to extract quantitative information on cell elasticity and fluidity of leukaemia cells (HL-60). To avoid the use of expensive high-speed cameras, researchers have developed impedance-based detection methods to profile cell biophysical properties by quantifying the cell geometrical change, 178 or cell creeping process 179 in an optics-free and label-free manner. A recent study was reported by Petchakup et al who defined a novel "electrical deformability index" for single cell electro-mechano-phenotyping (Fig.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…[12][13][14][15][16][17][18] So far, IFC techniques have made progress in high-content measurement of single-cell biophysical multi-modal fingerprints including cell size, 19 shape, 20 and electrical [21][22][23] and mechanical properties. 24,25 Most of the IFC techniques use a narrow channel [26][27][28][29][30][31][32][33] as mechanical constriction (MC) to decrease the sensing aperture (SA), which matches the cell size to achieve high detection sensitivity. Frequently, MC refers to impedance cytometers housing a "constriction channel", whose dimensions are smaller than that of the cells under investigation, so that a mechanical deformation of the cells is induced.…”
Section: Introductionmentioning
confidence: 99%
“…Cellular mechanical properties are closely associated with cell status and disease, including cellular senescence, cellular storage lesions, sickle cell, and sepsis, as they reflect the internal structure changes of cells. Thus, biomechanical analysis is promising to identify cell states, , diagnose cancer, detect rare cells, etc. , For instance, the stiffness of red blood cells (RBCs) gradually increases in the cryogenic storage environment of blood banks as the duration of storage lengthens, so monitoring the cellular mechanical properties is essential for prescreening of blood to reduce the risk of transfusion. , …”
mentioning
confidence: 99%